THE ROLE OF INTERNAL AUDIT IN IMPROVING REGIONAL FINANCIAL INTEGRITY (A STUDY OF THE GORONTALO PROVINCIAL INSPECTORATE) - Andi Balqis Rahmashari Ashari; Rio Monoarfa; Titi Umi Kalsum Hulopi (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the role of internal audit in enhancing the integrity of regional financial reports at the Gorontalo Provincial Inspectorate. The research employed a descriptive qualitative method, collecting data through in-depth interviews, observations, and document studies. The results indicate that internal audit plays a significant role through assurance, consultative, and risk-based supervisory functions, including regular audits, OPD financial report reviews, technical assistance, probity audits, and investigative audits. However, supervisory effectiveness is constrained by limited authority, resources, and OPD commitment. To overcome these challenges, the Inspectorate implements strategies such as utilizing information technology, improving coordination with OPDs, monitoring follow-up on audit recommendations, and ensuring auditor independence. These findings demonstrate that internal audit contributes to increased accountability and prevention of financial irregularities. The study offers practical implications for enhancing auditor capacity and OPD coordination, as well as recommendations for future research to broaden the scope of informants.